Caracterização geológica-geofísica do meio aqüífero fissural : uma contribuição aos modelos de fluxo e armazenamento de água subterrânea - Silva, Carlos Cesar Nascimento da (2004)
Northeastern Brazil is mainly formed by crystalline terrains (around 60% in area). Moreover, this region presents a semi-arid climate so that it is periodically subject to drought seasons. Furthermore, ground water quality extracted fromwells usually presents poor quality because of their high salinity contents. Nevertheless, ground water is still a very important source of water for human and animal consumption in this region. Well sitting in hard rocks terrains in Northeastern Brazil offers a mean success index of aboul 60%, given that a successful siting is defined by a well producing at least 0.5 m³/h. This low index reveals lack of knowledga about the true conditions of storage and percolation of ground water in crystalline rocks. Two models for structures storing and producing ground water in crystalline rocks in Northeastem Brazil have been proposed in the literature. The first model,tradnionally used for well sitting since the sixties are controlled by faults or fractures zones. This model is commonly referred, in Brazilian hydrogeological literature, as the "creek-crack" model (riacho-fenda in Portuguese). Sites appearing to present dense drainage network are preferred for water well siting - particularly at points where the drainages cross-cul each other. Field follow up work is usually based only on geological criteria. The second model is the "eluvio-alluvial through" (calha eluvio-aluvionar in Portuguese); it is also described in the literature but it is not yet incorporated in well sitting practice. This model is based on the hypothesis that reclilinear drainages can also be controlled by the folietion of the rock. Eventually, depending upon the degree of weathering, a through-shaped structure filled with sediments (alluvium and regolith) can be developed which can store and water can be produced from. Using severalfield case studies, this Thesis presents a thorough analysis ofthe two above cited models and proposes a new model. The analysis is based on an integrated methodological approach using geophysics and structural geology. Both land (Resitiviy and Ground Penetrating Radar- GPR) and aerogeophysical (magnetics and frequency domain eletromagnetics) surveys were used. Slructural analysis emphasized neolectonic aspects; in general, itwas found that fractures in the E-W direction are relatively open, as compared to fracturas inthe N-S direction, probably because E-W fractures were opened by the neotectonic stress regime in Northeastern Brazil, which is controlled by E-W compression and N-S extension. The riacho-fenda model is valid where drainages are controlled by fractures. The degree of fracturing and associated weathering dictale the hydrogeological potential of the structure. Field work in structural analogues reveals that subvertical fractures show consistent directions both in outcrop and aerophotograph scales. Geophysical surveys reveal subvertical conductive anomalies associated to the fracture network controlling the drainage; one of the borders of the conductive anomaly usually coincide wih the drainage. An aspect of particular importance to the validation of fracture control are the possible presence of relalively deep conductive anomalies wihoul continuation or propagalion to the surface. The conductive nature of lhe anomaly is due to the presence of wealhered rock and sedirnenls (alluvium and/or regolilh) storing ground waler which occur associated to the fracture network. Magnetic surveys are not very sensisnive to these structures.lf soil or covering sedirnents are resislive (> 100 Ohm.m), GPR can ba used to image precisely lhe fracture network. A major limialion of riacho-fenda model, revealed by GPR images, is associated to the fact thal subhorizontal fractures do play a very important role in connecting the fracture network, besides connect shallow recharge zones to relalively deep subvertical frecture zones. Iffractures play just a secondary control on the drainage, however, r/acho-fenda model may have a very limiled validny; in these cases, large portions oflhe drainage do nol coincide wilh frectures and mosl oflhewells localed in lhe drainage surrounding would resull dry. Usually, a secondary conlrol on lhe drainage by Ihefraclure networkcan be revealed only wilh detailed geophysical survey. The calha elClv1o-aluvlonarmodel is valid where drainages are conlrolled by folialion. The degree 01 wealhering 01 lhe lolialion planes dictales lhe hydrogeological polenlial 01 lhe slruclure. Outcrop analysis reveals Ihal lolialion and drainage direclions are parallel and Ihal no Iraclures, orfraclures wilh diflerent directions 01 lhe drainage direclion occur. Geophysical surveys reveal conduclive anomalies in a slab lorm associaled 10 lhe Ihrough 01 lhe wealhered rock and sedimenls (alluvium and/or regolith). Magnelic surveys can ofler a very good conlrol on lolialion direclion. An importanl aspect 10 validale lolialion conlrol are lhe presence 01 conductive anomalies showing shallow and deep portions area which are linked. Illhere is an exlensive soil cover, r/acho-fenda and calha eIClv1o-aluv/onar conlrols can be easily misinlerpreled in lhe absence 01 geophysical conlrol. Certainly, Ihis lacl could explain at leasl a part of lhe failure index in well sitting. The model wealhering sack (bolsllo de Intempertsmo in Portuguese) is proposed to explain cases where a very inlensive wealhering occur over lhe crystalline rock so Ihal a secondary inlerslilial porosity is crealed. The waler is Ihen stored in lhe porous of lhe regolilh in a similar mannerlo sedimentary rocks. A possible example ofthis model was delecled by using land geophysical survey where a relalivelyvery deep isolaled conduclive anomaly, in a slab form, was delected. Iflhis structure does store ground waler, certainly Ihere must be a link 01 lhe deep slructure wilh lhe surface in orderlo provide walerfeeding. This model mighl explain anomalous waler yields as greal as 50 m³/h Ihalsomelimescan occur in crystalline rocks in Northeaslern Brazil